Composite photo-thermal film, preparation method and high-salinity wastewater treatment device containing composite photo-thermal film

By loading carbon/iron sulfide on the hydrophilic filter membrane and hydrophobic modification, a composite photothermal film is formed, which solves the problems of high energy consumption and high cost of the existing ammonium sulfate wastewater treatment methods, and achieves efficient photothermal evaporation and purification effect.

CN119390166AActive Publication Date: 2025-02-07NANJING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411548874.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing desalination treatment methods for ammonium sulfate wastewater have problems such as high energy consumption, high cost, and possible secondary pollution. There are no reports of using solar interface evaporation technology to treat ammonium sulfate wastewater.

Method used

A composite photothermal film is used, which uses a hydrophilic filter membrane as a carrier, is loaded with carbon/ferrous sulfide, and forms a Janus structure through hydrophobic modification, which improves the anti-salt deposition performance of the film and achieves efficient photothermal evaporation.

Benefits of technology

It achieves excellent photothermal evaporation rate and photothermal conversion efficiency, and can purify ammonium sulfate wastewater under solar light drive, reduce energy consumption and cost, and ensure high evaporation efficiency under long-term continuous operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390166A_ABST
    Figure CN119390166A_ABST
Patent Text Reader

Abstract

The invention discloses a composite photo-thermal film which is characterized in that a hydrophilic filter membrane is used as a carrier, and carbon / iron sulfide is loaded on the carrier; wherein a hydrophobic group is grafted on one side, loaded with the carbon / iron sulfide, of the hydrophilic filter membrane. The invention also discloses a preparation method of the composite photo-thermal film, which comprises the following steps: (1) carrying out heat treatment on the coal slime, and carbonizing the coal slime; (2) mixing the carbonized coal slime with pyrite, and then carrying out high-temperature calcination in an inert atmosphere to obtain carbon / iron sulfide powder; (3) dispersing the carbon / iron sulfide powder into a solvent, performing ultrasonic treatment, and loading the carbon / iron sulfide powder onto a hydrophilic filter membrane through vacuum filtration; (4) carrying out one-side hydrophobic modification on the hydrophilic filter membrane obtained in the step (3) by using a polyethylene glycol solution containing a hydrophobic agent in a vacuum filtration manner to obtain a composite photo-thermal membrane with a Janus structure with a hydrophobic surface layer and a hydrophilic lower layer; wherein the side loaded with the carbon / iron sulfide is a hydrophobic side. The invention finally discloses a high-salinity wastewater treatment device containing the composite photo-thermal film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite photothermal film, and also relates to a preparation method of the composite photothermal film and a high-salt wastewater treatment device containing the composite photothermal film, belonging to the technical field of high-salt wastewater treatment. Background Art

[0002] Wastewater discharged from processes such as biomass energy production, amino alcohol production and fuel cell production usually contains a large amount of ammonium sulfate. If not handled properly, it may release ammonia gas to pollute the air and endanger human health.

[0003] Currently, common methods for desalination of ammonium sulfate wastewater include reverse osmosis, electrodialysis, ion exchange, evaporation crystallization, and calcium hydroxide precipitation. However, calcium hydroxide precipitation produces a large amount of precipitate, which may cause secondary pollution; ion exchange requires regular resin replacement, and waste resin disposal is complex and costly; electrodialysis consumes a lot of energy and has a limited scope of application; reverse osmosis is easily affected by changes in water quality and produces a large amount of concentrated wastewater that requires treatment, resulting in high operating costs; and evaporation crystallization has high treatment efficiency but consumes a lot of energy.

[0004] Solar interfacial evaporation technology uses solar energy to heat and evaporate wastewater, effectively removing impurities and dissolved matter from the wastewater. Currently, there are no reports on the use of solar interfacial evaporation technology to treat ammonium sulfate wastewater. Summary of the Invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a composite photothermal film having excellent photothermal evaporation rate and photothermal conversion efficiency; another purpose of the present invention is to provide a method for preparing the above-mentioned composite photothermal film and a high-salt wastewater treatment device containing the above-mentioned composite photothermal film.

[0006] Technical solution: The composite photothermal film described in the present invention uses a hydrophilic filter membrane as a carrier, and carbon / iron sulfide is loaded on the carrier; wherein, a hydrophobic group is grafted on one side of the hydrophilic filter membrane loaded with carbon / iron sulfide.

[0007] The carbon / iron sulfide loading on the carrier is 1-3 mg / cm 2 .

[0008] The method for preparing the composite photothermal film comprises the following steps:

[0009] (1) heat treating the coal slime to obtain a coal-based carbon material;

[0010] (2) mixing the carbonized coal slime obtained in step (1) with pyrite, and calcining the mixture at a high temperature under an inert atmosphere to obtain a carbon / iron sulfide powder;

[0011] (3) dispersing the carbon / iron sulfide powder of step (2) in a solvent, ultrasonically treating the powder, and then loading the carbon / iron sulfide onto a hydrophilic filter membrane by vacuum filtration;

[0012] (4) The hydrophilic filter membrane obtained in step (3) is hydrophobically modified by vacuum filtration using a polyethylene glycol solution containing a hydrophobic agent to obtain a composite photothermal membrane with a Janus structure having a hydrophobic surface layer and a hydrophilic lower layer; wherein the side loaded with carbon / iron sulfide is the hydrophobic side.

[0013] If the surface of the composite photothermal membrane is not modified to be hydrophobic, salt crystals will precipitate on the membrane surface, affecting both the evaporation process and the collection of salt crystals.

[0014] Wherein, in step (2), the mixing mass ratio of pyrite and carbonized coal slime is 1:2; the calcination temperature is 500-1000° C., and the calcination time is 5-8 hours.

[0015] Wherein, in step (3), the hydrophilic filter membrane is one of a polyethersulfone filter membrane, a PVDF membrane, a cellulose acetate filter membrane, a mixed cellulose filter membrane or a nitrocellulose filter membrane.

[0016] Wherein, in step (4), the hydrophobic agent is prepared by mixing glacial acetic acid, trimethoxy(1H,1H,2H,2H-heptadecafluorodecyl)silane and isopropyl alcohol in a volume ratio of 0.1-2.0:0.5-2.0:96.0-98.0.

[0017] Wherein, in step (4), the volume ratio of the hydrophobic agent to the polyethylene glycol solution is 1:80-100.

[0018] A high-salt wastewater treatment device containing the above-mentioned composite photothermal membrane includes a reaction chamber for holding the wastewater to be treated and a water transfer layer for transferring the wastewater to the composite photothermal membrane; the composite photothermal membrane is laid above the waste liquid to be treated in the reaction chamber; and further includes a water guide layer and a salt collection layer, the composite photothermal membrane is arranged in the central area of ​​the water guide layer, the salt collection layer is laid on the side of the water guide layer away from the photothermal membrane, and the coverage area of ​​the salt collection layer is the periphery of the area of ​​the water guide layer where the photothermal membrane is placed.

[0019] It also includes a heat insulation layer, which is fixed on the reaction cavity. The water transmission layer passes through the heat insulation layer and is connected to the water guide layer. The water guide layer transmits water to the composite photothermal film.

[0020] The water transmission layer and the water guide layer are both non-woven fabrics, towel cloths or highly absorbent non-woven fabrics; the heat insulation layer is one of polystyrene foam, polyurethane foam or polyisocyanate foam; and the salt collection layer is a metal plate, a glass plate or a plastic plate.

[0021] The composite photothermal membrane produced by this invention modifies the surface of one side of a hydrophilic filter membrane by forming a hydrophobic substance (silicon-oxygen bond), resulting in a Janus structure with a hydrophilic bottom layer and a hydrophobic surface layer. This prevents wetting of the membrane's upper surface and improves the membrane's resistance to salt deposition. When treating saline wastewater, water evaporation is confined within the membrane, promoting spontaneous downward diffusion of salt, preventing salt condensation on the membrane surface, and ensuring the stability of the membrane structure and evaporation efficiency, enabling the membrane to maintain a high evaporation rate even during long-term continuous operation.

[0022] Beneficial effects: Compared with the existing technology, the present invention has the following significant advantages: the composite photothermal film prepared by the present invention has excellent photothermal evaporation rate, photothermal conversion efficiency and performance stability, and can be used to construct an interface evaporation device. Driven by sunlight, it can purify ammonium sulfate wastewater and obtain ammonium sulfate crystals, thereby realizing the diversified utilization of high-salt wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the structure of the high-salt wastewater treatment device in Example 1 of the present invention;

[0024] Figure 2 The wastewater quality change curve of the composite photothermal film formed by carbon / iron sulfide obtained at different calcination temperatures treating 10wt% ammonium sulfate wastewater for 2h under 1sun irradiation;

[0025] Figure 3 This is a comparison chart of the evaporation rate and photothermal conversion efficiency of the composite photothermal film formed by carbon / iron sulfide obtained at different calcination temperatures when treating 10wt% ammonium sulfate wastewater for 2 hours under 1sun irradiation;

[0026] Figure 4 The wastewater quality change curve of different photothermal films treating 10wt% ammonium sulfate wastewater for 2h under 1sun irradiation;

[0027] Figure 5 This is a bar graph of the evaporation rate at different times when the composite photothermal film of Example 1 treats 10 wt% ammonium sulfate wastewater under 1 sun irradiation;

[0028] Figure 6 This is a photo of a drop of water on the surface of the hydrophobically modified composite photothermal film (circular) prepared in Example 1. DETAILED DESCRIPTION

[0029] Example 1

[0030] The method for preparing the composite photothermal film of the present invention comprises the following steps:

[0031] (1) Preparation of carbonized coal slime: 0.5 g of coal slime was placed in a porcelain boat, placed in a tube furnace, and calcined at 800 °C for 2 h (heating rate of 5 °C min-1) under nitrogen. -1 , the cooling method is natural cooling), taking out after calcination, and grinding to obtain carbonized coal slime powder;

[0032] (2) Preparation of carbon / iron sulfide (carbon composite iron sulfide): 30 mg of carbonized coal slime and pyrite were dissolved in 100 mL of isopropanol aqueous solution (isopropanol aqueous solution was prepared by 60 mL of isopropanol and 40 mL of water) at a mass ratio of 2:1. After ultrasonic dispersion, the mixed solid material was collected by filtration and dried in a 60°C oven for 2 h; then placed in a 600°C tubular furnace and calcined for 6 h (nitrogen condition, heating rate of 5°C·min -1 , the cooling method is natural cooling), and the calcined product is taken out to obtain carbon / iron sulfide powder;

[0033] (3) 30 mg of carbon / iron sulfide powder was dispersed in 100 mL of isopropanol solution, wherein the isopropanol solution was prepared by 60 mL of isopropanol and 40 mL of water; after ultrasonic stirring for 30 min, the carbon / iron sulfide was loaded onto the PVDF membrane by vacuum filtration;

[0034] (4) 5 mL of polyethylene glycol and 20 mL of deionized water were mixed to obtain a polyethylene glycol solution; 250 μL of a hydrophobic agent (the hydrophobic agent was prepared by mixing 50 μL of glacial acetic acid, 200 μL of trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane and 9.75 mL of isopropanol) was added to the polyethylene glycol solution to obtain a mixed solution, which was loaded onto the surface of the PVDF membrane obtained in step (3) by vacuum filtration to obtain a composite photothermal membrane having a hydrophobic surface layer and a hydrophilic lower layer Janus structure; wherein the loading amount of carbon / iron sulfide on the PVDF membrane was 2.39 mg / cm 2 .

[0035] pass Figure 6 It can be seen that the PVDF membrane prepared in the present invention has good hydrophobic properties after the carbon / iron sulfide-loaded side (upper surface) is subjected to hydrophobic modification treatment.

[0036] Example 2

[0037] like Figure 1As shown, a high-salt wastewater treatment device containing the composite photothermal membrane of Example 1 is constructed, including a reaction chamber for holding the wastewater to be treated and a thermal insulation layer placed on the reaction chamber; it also includes a composite photothermal membrane, a water guide layer, a salt collection layer and a water transmission layer; one end of the water transmission layer is located in the wastewater, and the other end passes through the thermal insulation layer and is connected to the water guide layer, the water guide layer is laid on the thermal insulation layer, the composite photothermal membrane is laid in the central area of ​​the water guide layer, the salt collection layer is laid on the side of the water guide layer away from the photothermal membrane, and the coverage area of ​​the salt collection layer is the periphery of the area where the water guide layer is placed with the photothermal membrane.

[0038] The composite photothermal film is square in shape and laid in the central area of ​​the water guide layer; the water guide layer is an irregularly shaped non-woven fabric, which is used to store and transfer water transported from the water transfer layer to the composite photothermal film. The center of the irregularly shaped water guide layer is square and is used to place the composite photothermal film. A trapezoidal structure is extended on each side of the square of the water guide layer. The salt collection layer is laid in the trapezoidal structure area corresponding to the water guide layer and is away from the side of the photothermal film; the insulation layer is polystyrene foam, which is used to avoid errors caused by water evaporation due to direct sunlight shining on the water body; the water transfer layer is non-woven fabric, and ammonium sulfate wastewater passes through the non-woven fabric (water transfer layer) through the insulation layer to the water guide layer to ensure sufficient water source during the interface evaporation process; between the water guide layer and the insulation layer, aluminum foil is laid under the trapezoidal part extending from the central square of the water guide layer to receive salt crystals formed on the edge of the composite photothermal film during the interface evaporation process.

[0039] The high-salt wastewater treatment device of Example 2 was used to treat 10 wt% ammonium sulfate wastewater under 1 sun irradiation for 2 h. By comparing the changes in water quality before and after the experiment, it can be seen that the evaporation rate of the composite photothermal film is 1.93 kg·m -2 ·h -1 , the photothermal conversion efficiency is 113.6%.

[0040] Comparative Example 1

[0041] The method for preparing the composite photothermal film in Comparative Example 1 is basically the same as that in Example 1, with the only difference being that in step (2), the calcination temperature is 300° C. to obtain the composite photothermal film.

[0042] Comparative Example 2

[0043] The method for preparing the composite photothermal film in Comparative Example 2 is basically the same as that in Example 1, with the only difference being that in step (2), the calcination temperature is 450° C. to obtain the composite photothermal film.

[0044] Comparative Example 3

[0045] The method for preparing the composite photothermal film in Comparative Example 3 is basically the same as that in Example 1, with the only difference being that in step (2), the calcination temperature is 800° C. to obtain the composite photothermal film.

[0046] Comparative Example 4

[0047] The method for constructing a high-salt wastewater treatment device in Comparative Example 4 is basically the same as that in Example 2, with the only difference being that no composite photothermal film is laid in the central area of ​​the water guide layer and no light source is added.

[0048] Comparative Example 5

[0049] The method for constructing a high-salt wastewater treatment device in Comparative Example 5 is basically the same as that in Example 2, with the only difference being that a pure PVDF membrane (without carbon / iron sulfide material loading and hydrophobic modification) is laid in the central area of ​​the water guide layer.

[0050] Comparative Example 6

[0051] Comparative Example 6 is essentially the same as Example 2 in constructing a high-salt wastewater treatment device, with the only difference being that a carbonized coal slime membrane is laid in the central region of the water guide layer. The preparation method of the carbonized coal slime membrane is essentially the same as the method for preparing the composite photothermal membrane in Example 1, with the only difference being that in step (2), no pyrite is added to obtain the carbonized coal slime membrane, and the loading of coal-based carbon on the PVDF membrane is the same as the loading of carbon / iron sulfide in Example 1.

[0052] The photothermal films of Example 1 and Comparative Examples 1 to 3 are used to construct a high-salt wastewater treatment device, and the device construction process is the same as that of Example 2. Figure 2 、 Figure 3 It can be found that the evaporation rate and photothermal conversion efficiency of the composite photothermal film obtained at 300℃, 450℃, 600℃ and 800℃ are respectively: 1.42kg·m -2 ·h -1 and 82.5%, 1.77 kg·m -2 ·h -1 and 100.7%, 1.93 kg·m -2 ·h -1 and 113.6%, 1.71 kg·m -2 ·h -1 and 105.2%, so the composite photothermal film prepared in Example 1 has the fastest evaporation rate and the best photothermal conversion efficiency.

[0053] The evaporation rate of the high-salt wastewater treatment device constructed by comparing Example 2 with Comparative Examples 5 to 6 in treating 10 wt% ammonium sulfate wastewater for 2 hours under 1 sun irradiation is as follows: Figure 4 It can be seen that the dark evaporation rate of ammonium sulfate wastewater obtained by the treatment device constructed in Comparative Example 4 is 0.34 kg·m -2 ·h -1 The evaporation rate of the pure PVDF membrane treatment device constructed in Comparative Example 5 is 0.88 kg·m -2 ·h-1 The evaporation rate of the carbonized coal slime membrane treatment device constructed in Comparative Example 6 is 1.32 kg·m -2 ·h -1 The evaporation rate of the composite photothermal film processing device prepared in Example 2 is 1.93 kg·m -2 ·h -1 .

[0054] The high-salt wastewater treatment device prepared in Example 1 was used to treat 10 wt% ammonium sulfate wastewater under 1 sun irradiation, and the evaporation rates of the device at different operating times were compared. Figure 5 It can be seen that under the continuous operation of up to 12 hours, the evaporation rate of the device is basically 1.93 kg·m -2 ·h -1 Up and down, and the fluctuation range is very small.

[0055] The photothermal material of the present invention is made by high-temperature calcination of coal slime and pyrite, wherein the coal slime is a solid waste. After high-temperature calcination, the obtained composite material has excellent photothermal efficiency and stability, which not only reduces production costs but also realizes the resource utilization of waste and reduces environmental pollution.

Claims

1. A composite photothermal film, characterized in that: The composite photothermal film uses a hydrophilic filter membrane as a carrier, and carbon / iron sulfide is loaded on the carrier; wherein a hydrophobic group is grafted on one side of the hydrophilic filter membrane loaded with carbon / iron sulfide.

2. The composite photothermal film according to claim 1, characterized in that: The loading amount of carbon / iron sulfide on the carrier is 1-3 mg / cm 2 .

3. The method for preparing the composite photothermal film according to claim 1, characterized in that: The steps include: (1) thermally treating coal slime to obtain coal-based carbon material; (2) mixing the carbonized coal slime obtained in step (1) with pyrite, and calcining the mixture at a high temperature under an inert atmosphere to obtain a carbon / iron sulfide powder; (3) dispersing the carbon / iron sulfide powder of step (2) in a solvent, and after ultrasonic treatment, loading the carbon / iron sulfide onto a hydrophilic filter membrane by vacuum filtration; (4) The hydrophilic filter membrane obtained in step (3) is subjected to hydrophobic modification on one side by vacuum filtration using a polyethylene glycol solution containing a hydrophobic agent to obtain a composite photothermal membrane with a Janus structure having a hydrophobic surface layer and a hydrophilic lower layer; wherein the side loaded with carbon / iron sulfide is the hydrophobic side.

4. The method for preparing the composite photothermal film according to claim 3, characterized in that: In step (2), the mixing mass ratio of pyrite to carbonized coal slime is 1:2; the calcination temperature is 500-1000° C., and the calcination time is 5-8 hours.

5. The method for preparing the composite photothermal film according to claim 3, characterized in that: In step (3), the hydrophilic filter membrane is one of a polyethersulfone filter membrane, a PVDF membrane, a cellulose acetate filter membrane, a mixed cellulose filter membrane or a nitrocellulose filter membrane.

6. The method for preparing the composite photothermal film according to claim 3, characterized in that: In step (4), the hydrophobic agent is prepared by mixing glacial acetic acid, trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane and isopropanol in a volume ratio of 0.1-2.0:0.5-2.0:96.0-98.

0.

7. The method for preparing the composite photothermal film according to claim 3, characterized in that: In step (4), the volume ratio of the hydrophobic agent to the polyethylene glycol solution is 1:80-100.

8. The high-salt wastewater treatment device of the composite photothermal membrane according to claim 1 is characterized in that: It includes a reaction chamber for containing wastewater to be treated and a water transfer layer for transferring the wastewater to a composite photothermal membrane; the composite photothermal membrane is laid above the waste liquid to be treated in the reaction chamber; it also includes a water guide layer and a salt collection layer, the composite photothermal membrane is arranged in the central area of ​​the water guide layer, the salt collection layer is laid on the side of the water guide layer away from the photothermal membrane, and the coverage area of ​​the salt collection layer is the periphery of the area where the water guide layer is placed on the photothermal membrane.

9. The high-salinity wastewater treatment device according to claim 8, characterized in that: It also includes a heat insulation layer, which is placed on the reaction chamber. The water transmission layer passes through the heat insulation layer and is connected to the water guide layer, and the water guide layer transmits water to the composite photothermal film.

10. The high-salinity wastewater treatment device according to claim 8 or 9, characterized in that: The water transmission layer and the water guide layer are both non-woven fabrics, towel cloth or highly absorbent non-woven fabrics; the heat insulation layer is one of polystyrene foam, polyurethane foam or polyisocyanate foam; and the salt collection layer is a metal plate, a glass plate or a plastic plate.

Citation Information

Patent Citations

  • Double-sided photo-thermal conversion material and solar seawater evaporation device constructed by same

    CN111924918A

  • Hydrophilic-hydrophobic Janus composite photo-thermal conversion material as well as preparation method and application thereof

    CN113005765A

  • MXene-doped photo-thermal distillation membrane as well as preparation method and application thereof

    CN116672894A

  • Method for synchronously activating persulfate through photo-thermo-FeS2 / dust-free cloth and application of method

    CN117654552A